HUBUNGAN ANTARA MOTIVASI BERPRESTASI DAN KEBIASAAN BELAJAR MATEMATIKA SISWA DENGAN PRESTASI BELAJAR SISWA - SAIFULLAH SAIFULLAH; MUCHLIS MUCHLIS (Program Studi Pendidikan Matematika, 2018)
This study aims to determine whether there is a relationship between achievement motivation and students' mathematics learning habits with student achievement. This research is a correlation study consisting of two independent variables, namely achievement motivation and students' mathematics learning habits, and one dependent variable, student learning achievement. The research was conducted in Bima City 5 Middle School Class VIII-B in 2017 with a sample of 23 people taken by proportional random sampling. The results of this study produce three conclusions, namely: There is a positive and significant relationship between achievement motivation and student achievement with a correlation coefficient (ry1) of 0.90 and a coefficient of determination (r1y1) of 90% with a regression equation Ŷ1 = 53.832 + 2.579X1. A positive and significant relationship between students' mathematical learning habits and student achievement, with a correlation coefficient (ry2) of 0.74 and a coefficient of determination (r²y2) of) 74% with a regression equation Ŷ1 = 7.102 + 0.742X2. Positive and significant relationship between achievement motivation and mathematics learning habits of students with student learning achievement with a correlation coefficient (ry12) of 0.830 and a coefficient of determination (r²y12) of 83% with a regression equation Ŷ12 = 3.177 +0.062 X1 + 0.753X2. The conclusion of this study is that student learning achievement can be improved through increasing achievement motivation and students 'mathematics learning habits as indicated by the determination coefficient of 0.830 which means the contribution of achievement motivation and students' mathematics learning habits with student learning achievement is 83%.